ECOLOGICAL COMPONENT AS AN INTEGRAL PART OF PROFESSIONAL EDUCATION OF UKRAINE (Innovative professional education, 2023)
The necessity of ecological competence formation in the students of vocational education during the mastering of working professions is substantiated.
Keywords: ecology, ecological competence, students, environment